Pressurized intraperitoneal aerosol chemotherapy with cisplatin and doxorubicin or oxaliplatin for peritoneal metastasis from pancreatic adenocarcinoma and cholangiocarcinoma. (July 2020) - Di Giorgio, Andrea; Sgarbura, Olivia; Rotolo, Stefano; Schena, Carlo Alberto; Bagalà, Cinzia; Inzani, Frediano; Russo, Andrea; Chiantera, Vito; Pacelli, Fabio
Background: Systemic chemotherapy for pancreatic adenocarcinoma (PDAC) and cholangiocarcinoma (CC) with peritoneal metastases (PM) is affected by several pharmacological shortcomings and low clinical efficacy. Pressurized intraperitoneal aerosol chemotherapy (PIPAC) is expected to maximize exposure of peritoneal nodules to antiblastic agents. This study aims to evaluate safety and efficacy of PIPAC for PM of PDAC and CC origin. Methods: This is a retrospective analysis of consecutive PDAC and CC cases with PM treated with PIPAC at two European referral centers for peritoneal disease. We prospectively recorded from August 2016 to May 2019 demographic, clinical, surgical, and oncological data. We performed a feasibility and safety assessment and an efficacy analysis based on clinical and pathological regression. Results: Twenty patients with PM from PDAC (14) and CC (six) underwent 45 PIPAC administrations. Cisplatin–doxorubicin or oxaliplatin were administered to eight and 12 patients, respectively. We experienced one intraoperative complication (small bowel perforation) and 18 grade 1–2 postoperative adverse events according to Common Terminology Criteria for Adverse Events version 4.0. A pathological regression was recorded in 50% of patients (62% in the cisplatin–doxorubicin cohort and 42% in the oxaliplatin one). Median survival from the first PIPAC was 9.7 and 10.9 months for PDAC and CC, respectively. Conclusion: PIPAC resulted feasible and safe without relevant toxicity issues, with both cisplatin–doxorubicin and oxaliplatin. The pathological response observed supports the evidence of antitumoral activity. Despite the study limitations, these outcomes are encouraging, recommending PIPAC in prospective, controlled trials in the palliative setting or the first line chemotherapy for PM from PDAC and CC.